Metabolism archetype cancer cells induce protumor TREM2+ macrophages via oxLDL-mediated metabolic interplay in hepatocellular carcinoma - Tianhao Chu; Guiqi Zhu; Zheng Tang; Weifeng Qu; Rui Yang; Haiting Pan; Yi Wang; Ruilin Tian; Leilei Chen; Zhiqi Guan; Yichao Bu; Qianfu Zhao; et al. (Nature Communications)
Abstract The functional programs adopted by cancer cells and their impact on the tumor microenvironment are complex and remain unclear. Here, we identify three distinct single-cell archetypes (i.e. metabolism, stemness and inflammation) in hepatocellular carcinoma (HCC) cells, each exhibiting unique spatial distribution. Further analysis shows an immune-suppressive niche populated by metabolism archetype cancer cells and TREM2-positive tumor-associated macrophages (TREM2+ TAMs), which exacerbates immune exclusion and compromises patient outcomes. Mechanistically, we demonstrate that the upregulated squalene epoxidase (SQLE) expression in metabolism archetype cancer cells facilitates the generation of oxidized LDL (oxLDL). OxLDL induces TREM2+ TAM polarization through the TREM2-SYK-CEBPα axis, enabling these TAMs to promote cancer cell invasion, resistance to effector cytokines and CD8+ T cell dysfunction. Importantly, cancer cell-intrinsic SQLE and TREM2+ TAMs are associated with inferior immunotherapy response in human and mouse HCC. Our results highlight an oxLDL-mediated metabolic interplay between cancer cells and TREM2+ TAMs, offering a promising therapeutic avenue for HCC immunotherapies.